Graphite to diamond transition induced by photoelectric absorption of ultraviolet photons - Ana I. Gómez de Castro (Nature Portfolio, 2021)
Abstract The phase transition from graphite to diamond is an appealing object of study because of many fundamental and also, practical reasons. The out-of-plane distortions required for the transition are a good tool to understand the collective behaviour of layered materials (graphene, graphite) and the van der Waals forces. As today, two basic processes have been successfully tested to drive this transition: strong shocks and high energy femtolaser excitation. They induce it by increasing either pressure or temperature on graphite. In this work, we report a third method consisting in the irradiation of graphite with ultraviolet photons of energies above 4.4 eV. We show high resolution electron microscopy images of pyrolytic carbon evidencing the dislocation of the superficial graphitic layers after irradiation and the formation of crystallite islands within them. Electron energy loss spectroscopy of the islands show that the sp2 to sp3 hybridation transition is a surface effect. High sensitivity X-ray diffraction experiments and Raman spectroscopy confirm the formation of diamond within the islands.